SAT0219 Shear-Wave Elastography: A New Imaging Method for Evaluating Scleroderma Skin. (10th June 2014) - Santiago, T.L.; Coutinho, M.; Salvador, M.J.; Del Galdo, F.; Redmond, A.; Da Silva, J.
Abstract : Background: Skin involvement is of major clinical and prognostic relevance in systemic sclerosis (SSc) and is often the primary outcome in clinical trials in SSc. Nevertheless, a fully validated, objective and sensitive measure of skin involvement is lacking. Shear-wave elastography in the form of Siemens' proprietary, Virtual Touch and Imaging Quantification (VTIQ), is an emerging, operator-independent technique, which can obtain absolute quantitative stiffness values. Objectives: To determine validity and reliability of VTIQ for evaluate skin stiffness as a measure of skin involvement in SSc. Methods: Twenty-six SSc patients were included (mean age was 55.3±12.1, mean disease duration 12.5 years (range 0.5-36), and mean mRSS 11.8 (range 0-33). Seventeen age and gender matched controls were recruited. Ultrasound evaluation was performed with a Siemens ACUSON S3000 ultrasound system. Each participant underwent an ultrasound exam at 16 Rodnan sites (face was excluded). The images consist of translucent colour maps superimposed on B-mode images, indicating soft through stiffer tissue and supplemented by tabulated absolute values for shear wave velocity (as a measure of the skin stiffness). Mean shear-wave velocities (in m/s) were obtained at each site by averaging three measurements made per image. Intraobserver reliability was calculated in four SSc patients and two healthy controls, in two different scanning sessions, one week apart. Results: The mean and SD absolute stiffness measures were (in m/s): chest –SSc 2.7±1.1 vs control 2.3±0.7, upperarm – SSc 2.9±1.0 vs control 2.2±0.3; forearm – SSc 3.1±1.1 vs control – 2.2±0.3; finger –SSc 4.3±2.0 vs control – 2.2±0.2; hand –SSc 4.0±1.5 vs control – 2.2±0.3; abdomen - SSc 2.4±0.8 vs control 2.0±0.4, thigh – SSc 2.6±0.4 vs control 2.1±0.2, leg – SSc 3, 1±0.9 vs control 2, 4±0, 4 and foot – SSc 3.2±0.9 vs control 2.3±0.2. Average skin stiffness increased with increasing skin scores for all regions studied other than hands (Figure 1 ). Two-tailed t-tests were performed to investigate whether differences between the means of patients and controls differed systematically at each site. Statistical significance (p<0.001) was achieved at the upperarm, hand, forearm, finger, thigh, leg and (p<0.01) at the foot. Statistical significance was not reached for the chest (p=0.15) and the abdomen (p=0.06). In addition, absolute skin stiffness measurements were higher in all clinically "unaffected" areas from SSc patients (defined as local mRSS =0) than in the controls, reaching statistical significance (p<0.001) at the forearm and hand, and (p<0.01) at the upperarm and finger. The technique showed very good intraobserver reliability in our small sample (intraclass correlation coefficients >0.8). Conclusions: Shear-wave elastography represents a feasible and reproducible quantitative method for assessing stiffness of the skin in scleroderma. It adds sensitivity to clinical evaluation, as even apparently normal skin in SSc patients presents increased shear-wave velocities values. Further research is required, but this early study supports the clinical and scientific potential of this new measure of skin involvement in SSc. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1213